2022
DOI: 10.1111/rec.13775
|View full text |Cite
|
Sign up to set email alerts
|

Coastal bird community response to dredge‐spoil tidal marsh restoration at New Round Island, Mississippi, U.S.A.

Abstract: The northern Gulf of Mexico has been the focus of many coastal habitat restoration projects in the wake of new funding streams stemming from the settlement of the 2010 Deepwater Horizon oil spill litigation. One such project was the creation of New Round Island (RNDI) in Mississippi, a 86 ha island created using dredge material in 2017. The island design incorporated a novel U-shaped sand berm with multiple interconnected containment sells. In this study we sought to document changes in relative abundance of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Dredge islands or other similar artificial sites are also commonly accepted and used for nesting by gulls and terns (Van Zoemeren et al ., 2019; Ritenour et al ., 2022). Indeed, construction of artificial islands has been used to compensate for the loss of previously used natural sites (Stienen et al ., 2005; Gamblin et al , 2022). In the present study, we found that dredge islands allow optimal productivity (0.9 fledglings per breeding attempt) for Sandwich Terns originally nesting early in the season and even from replacement clutches of late breeders (0.7 fledglings per breeding attempt).…”
Section: Discussionmentioning
confidence: 99%
“…Dredge islands or other similar artificial sites are also commonly accepted and used for nesting by gulls and terns (Van Zoemeren et al ., 2019; Ritenour et al ., 2022). Indeed, construction of artificial islands has been used to compensate for the loss of previously used natural sites (Stienen et al ., 2005; Gamblin et al , 2022). In the present study, we found that dredge islands allow optimal productivity (0.9 fledglings per breeding attempt) for Sandwich Terns originally nesting early in the season and even from replacement clutches of late breeders (0.7 fledglings per breeding attempt).…”
Section: Discussionmentioning
confidence: 99%
“…Dredge islands, built in the northern Po Delta over the last thirty years and those that will be built in the next years, may probably be suitable colony sites. Dredge islands or similar artificial sites are also commonly accepted and used for nesting by gulls and terns (Van Zomeren et al 2019, Ritenour et al 2022; sometimes, the building of artificial islands has been used as a way to compensate for the loss of previously used natural sites (Stienen et al 2005, Gamblin et al 2022. In southern France, the use of artificial colony sites led to an increase of 14% of Slender-billed Gulls in 2011−2017 (Schwartz et al 2022), while in the lagoon of Venice, several waterbirds regularly use dredge islands to nest (Scarton & Valle 2015, Scarton 2017.…”
Section: Discussionmentioning
confidence: 99%